Mechanistic Insight into the Enhanced Anti-Pulmonary Hypertension Efficacy of Wogonin Co-Amorphous - Zhongshui Xie; Yucai Chen; Jiaqi Xie; Yan Lei; Chunxue Jia; Yulu Liang; Hongjuan Wang; Jianmei Huang (Pharmaceutics)
Background: Pulmonary hypertension (PH) remains a life-threatening rare disease characterized by inflammation and oxidative stress in pulmonary artery smooth muscle cells (PASMCs). Wogonin (Wog), a plant-derived polyphenolic compound extracted from Scutellaria baicalensis Georgi, exhibits notable antioxidant activity and anti-PH efficacy, whereas its clinical applications are greatly limited by poor aqueous solubility. Methods: Herein, an innovative wogonin-aloperine co-amorphous (Wog-Alop) was developed to improve the aqueous solubility and, thus, anti-PH efficacy of Wog. Results: As expected, the aqueous solubility of Wog-Alop is about 40-fold that of Wog; meanwhile, the Wog-Alop demonstrates better oral bioavailability and anti-PH efficacy than Wog; moreover, the Wog-Alop exhibits significantly enhanced capacity to attenuate oxidative stress in human PASMCs compared to Wog. Conclusions: The results suggested that Wog-Alop could not only improve the solubility of Wog, thereby enhancing its oral bioavailability but also alleviate Wog’s oxidative stress effects. These synergistic effects ultimately culminate in the enhanced anti-PH efficacy of Wog. In summary, the present study developed an innovative co-amorphous strategy for the delivery of Wog and improved its anti-PH efficacy.